Digitalization and down streaming of Sumatra batik motifs as symbols of cultural heritage: turtle graphics as a tool for sustainable development - Prijono, Agus; Pandanwangi, Ariesa; Ratnadewi, Ratnadewi (International Journal of Visual and Performing Arts, 2024)
The importance of preserving Sumatra batik motifs as a cultural heritage is facing major challenges in the digital era. The problem of this research lies in the difficulties in digitalizing and commercializing batik motifs effectively and maintaining authenticity and cultural value. This article aims to explore the use of the Turtle Graphic as a tool for digitalizing and down-streaming Sumatra batik motifs. Turtle graphics were initially crafted as an instructive instrument for educational settings, paving the way for teachers to demonstrate drawing concepts. On a different note, it also serves convenience to coders needing graphic output - offering them a solution without necessitating more complicated or external libraries in their projects. The research method involves applying graphical programming (using Turtle graphics) to produce digital representations of batik motifs. The technical aspects of digitization implemented in the Turtle Graphic are (1) data identification, which is done by creating a table to select motifs that are currently rare; (2) motifs that have been identified are revitalized through making simple sketches; (3) sketches are made in digital Turtle Graphics to make it easier for MSMEs to document and implement into prototype batik models. One example of the batik motif used in this research is the Daun Sirih Melayu batik motif. This batik motif often uses images of betel leaves that are intertwined and sticking out.Â  The Daun Sirih Melayu batik motif was chosen as a representative example because the philosophical meaning of the betel leaf batik motif symbolizes a form of respect. Betel leaves are also important in tradition, especially at proposals, weddings, traditional title awards, and other events. The research results show that Turtle Graphics can simplify digitalization. These contribute to the preservation and socialization of Sumatra batik and support the sustainability and popularization of batik in an increasingly digital global context.Â  Academics can also use this research as a basis for further research, while for MSMEs, it is a good opportunity to implement it in batik centers in the archipelago, especially on Sumatra island.